Corruption and its relatives: facing the relationship between economic health and quality of government - Anna Rita Dipierro; Pierluigi Toma (Regional Studies, Regional Science)
The prevailing orientation in the existing literature on corruption is on its consequences for the socioeconomic dimensions, on a national basis. Using a promising proxy for quality of government (QoG) with substantial potential for further research, we examine the relationship between gross domestic product (GDP) per capita and QoG across 198 European regions from 2009–2022. We enrich the relatively sparse but relevant body of literature on this issue by testing and demonstrating that the reverse causality in this linkage should not be overlooked. We exploit the power of instrumental modelling in a panel data setting, allowing for the inclusion of a new perspective that fits with the place-based rationale of recent European policies. Beyond being of interest to researchers, the results are significant for policymakers and society as a whole.